Meningkatkan Rasa Percaya Diri Mahasiswa dalam Speaking English Melalui Kegiatan English BootCamp - Roudlotun Nurul Laili; Muhammad Nashir (Indonesian Journal Publisher, 2021)
In today's era of globalization, English competence is an essential aspect for the young generation to collaborate and compete globally. This activity is necessary because students often feel reluctant and insecure when communicating by using English in and outside the campus because they are afraid of making mistakes in pronunciation or grammatically. This community service activity aimed to increase students' motivation and self-confidence in Speaking English through the English BootCamp. English BootCamp is an outdoor activity that aims to give students a new atmosphere through more exciting activities. This activity was attended by 60 students who are the new members of Stikes Banyuwangi English Club. The expected outcome was that the students are more motivated to sharpen their skills and confidence in speaking English even though they majored in medicine. The methods used were games, discussion, songs, role play, and Free Talking. Students are very enthusiastic about joining this program because they provide a new experience with an outdoor atmosphere that is more relaxed, not boring, and not monotonous with various fun activity methods. Students become more courageous and have high self-confidence in Speaking English. They are more active in asking questions about vocabulary/expressions they do not understand, and they show their efforts by being actively involved in every activity. English BootCamp activity can change the students' mindset if Speaking English is not as difficult as imagined. This activity not only increases students' motivation and confidence but also their English skills.